Jobs or Amenities – What determines the migration balances of cities? - Annekatrin Niebuhr; Tanja Buch; Silke Hamann; Anja Rossen (European Regional Science Association (ERSA), 2012)
The population growth of cities in industrialized countries is characterized by striking disparities. While some cities experience a kind of resurgence in recent years others suffer from an ongoing depopulation. In this context an important issue refers to the question whether labour market conditions or amenities primarily account for the huge differences in cities' demographic prospects. We investigate the determinants of migration balances of German cities focusing on mobility of workers and the significance of jobs and amenities. With investigating cities' migration balances we choose a rather direct measure of urban attractiveness – in contrast to studies that use employment growth or other indicators. Both the striking and persistent disparities in labour market performance and amenities across cities and the high internal migration – in particular between East and West Germany – predestine the country for an analysis of the determinants of urban migration balances. Moreover, massive demographic changes are already visible in several regions, notably in East Germany, and affect the economic and social perspectives of cities. The regression analysis rests on a panel data set that covers the period from 2000 to 2007. In order to deal with unobserved heterogeneity and bias due to endogenous regressors fixed effects models and instrument variable estimation are applied. Our results suggest that different groups of factors influence the urban net migration rates. Local labour market conditions influence the mobility decision but amenities matter too. There is some indication that relatively high wages, low unemployment and especially the creation of new jobs attracts mobile workers. Moreover, the quality of life that a city offers is an important factor for the migration balance. This is in particular reflected by the robust effects of the urban recreation area and the average flat size. Our findings also point to relevance of climatic conditions and accessibility. Beyond we identify a size effect, i.e. large cities seem to be ceteris paribus more attractive than small cities. This suggests that agglomeration economies impact on the migration decision of workers. Residents of larg cities seem to benefit from consumption of goods such as theatres and other cultural infrastructure that are only supplied if demand exceeds a certain threshold. But the positive correlation between city size and region specific effects might also reflect matching externalities that arise in large (labour) markets.
Keywords: 330